The conserved bud20 zinc finger protein Is a new component of the ribosomal 60S subunit export machinery - Baßler, Jochen; Kallas, Martina; Thomson, Emma; Bradatsch, Bettina; Hurt, Ed (Molecular and cellular biology, 2012)
The nuclear export of the preribosomal 60S (pre-60S) subunit is coordinated with late steps in ribosome assembly. Here, we show that Bud20, a conserved C2H2-type zinc finger protein, is an unrecognized shuttling factor required for the efficient export of pre-60S subunits. Bud20 associates with late pre-60S particles in the nucleoplasm and accompanies them into the cytoplasm, where it is released through the action of the Drg1 AAA-ATPase. Cytoplasmic Bud20 is then reimported via a Kap123-dependent pathway. The deletion of Bud20 induces a strong pre-60S export defect and causes synthetic lethality when combined with mutant alleles of known pre-60S subunit export factors. The function of Bud20 in ribosome export depends on a short conserved N-terminal sequence, as we observed that mutations or the deletion of this motif impaired 60S subunit export and generated the genetic link to other pre-60S export factors. We suggest that the shuttling Bud20 is recruited to the nascent 60S subunit via its central zinc finger rRNA binding domain to facilitate the subsequent nuclear export of the preribosome employing its N-terminal extension.
Published ahead of print 8 October 2012
Gesehen am 11.09.2018